The Effect Of Animosity On Purchase Intention: Product Judgment As A Mediating Variable For Israeli Products (Mcdonald's) - Magdalena Polonia Rusik; Wenny Pebrianti; Juniwati Juniwati; Ramadania Ramadania (UNIVED Press, 2025)
This study aims to determine the effect of animosity on purchase intention on affiliated Israeli products (McDonald's) and to determine the role of product judgement in mediating animosity and purchase intention. Data were collected through an online survey of consumers who boycotted Israeli products. This research is quantitative research and the data collection was carried out using purposive sampling technique with a total of 150 respondents to be analysed. The data analysis method used is Warp-PLS. The results of this study found that animosity significantly affects purchase intention, animosity significantly affects product judgment, product judgment significantly affects purchase intention, and the relationship between animosity and purchase intention is mediated by product judgment.